USING INNOVATIVE METHODS AND GADGETS TEACHING ENGLISH EFFECTIVELY - Ravshanjonova , Diyora Ravshanjon qizi (Educational Research in Universal Sciences, 2023)
In the modern world, using electronic devices to learn a language is common knowledge. Today, both educational institutions and students rely on technology to properly teach and learn. Both teachers and students benefit from technological tools in the teaching and learning process. One should learn how to use technology devices to advance his job. Depending on their attitude, aptitude, and skill, the learners can learn more than two subjects at once thanks to technology advancements. In this article, we study how technology aids in both language teaching and learning.The article discusses the new types of pedagogical methods in teaching English and the methods of its application in the classroom, as well as the practical importance of the effective use of methods. Therefore, it is noted that these methods are useful for students to master another language and speak it fluently.